Stem cell transplantation can provide durable disease control in blastic plasmacytoid dendritic cell neoplasm: a retrospective study from the European Group for Blood and Marrow Transplantation - Roos-Weil, Damien; Dietrich, Sascha; Boumendil, Ariane; Polge, Emmanuelle; Bron, Dominique; Carreras, Enric; Iriondo Atienza, Arturo; Arcese, William; Beelen, Dietrich W.; Cornelissen, Jan J.; Kröger, Nicolaus; Milone, Giuseppe; et al. (Blood, 2013)
Patients with blastic plasmacytoid dendritic cell neoplasm (BPDCN) have a poor prognosis with conventional chemotherapy. In the present study, we retrospectively analyzed the outcome of patients with BPDCN who underwent allogeneic stem cell transplantation (allo-SCT) or autologous stem cell transplantation (auto-SCT). A total of 39 patients (allo-SCT, n = 34; auto-SCT, n = 5) were identified in the European Group for Blood and Marrow Transplantation registry. The 34 allo-SCT patients had a median age of 41 years (range, 10-70) and received transplantations from sibling (n = 11) or unrelated donors (n = 23) between 2003 and 2009. MAC was used in 74% of patients. Nineteen allo-SCT patients (56%) received transplantations in first complete remission. The 3-year cumulative incidence of relapse, disease-free survival, and overall survival was 32%, 33%, and 41%, respectively. By univariate comparison, being in first remission at allo-SCT favorably influenced survival, whereas age, donor source, and chronic GVHD had no significant impact. We conclude that high-dose therapy followed by allo-SCT from related or unrelated donors can provide durable remission even in elderly patients with BPDCN. However, it remains to be shown if graft-versus-malignancy effects can contribute significantly to BPDCN control after allo-SCT.
Prepublished online November 30, 2012
Gesehen am 19.01.2022